2013
DOI: 10.1371/journal.pone.0062041
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Public Health Interventions to Reduce the Health Impact of Climate Change: A Systematic Review of Systematic Reviews

Abstract: BackgroundClimate change is likely to be one of the most important threats to public health in the coming years. Yet despite the large number of papers considering the health impact of climate change, few have considered what public health interventions may be of most value in reducing the disease burden. We aimed to evaluate the effectiveness of public health interventions to reduce the disease burden of high priority climate sensitive diseases.Methods and FindingsFor each disease, we performed a systematic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 73 publications
2
73
0
3
Order By: Relevance
“…This includes improved methods for the assessment of the health implications of decisions in other sectors (such as in the energy and transport sectors and in the water, food and agriculture sectors), and the improved integration of climate change mitigation, adaptation and health through "settings-based" research; • improve decision-support, for example, research to improve vulnerability and adaptation assessments, operational predictions, and the understanding of decision-making processes; • improve the public's understanding of these issues, and into what interventions and mitigation strategies will be deemed acceptable to which constituencies; • estimate the costs of protecting health from the effects of climate change, including the characterisation of harmonized methods to estimate costs and benefits, the assessment of the health costs of inaction and the costs of adaptation, and improved economic assessment of the health co-benefits of climate and other environmental change mitigation [25,[130][131][132][133].…”
Section: Discussionmentioning
confidence: 99%
“…This includes improved methods for the assessment of the health implications of decisions in other sectors (such as in the energy and transport sectors and in the water, food and agriculture sectors), and the improved integration of climate change mitigation, adaptation and health through "settings-based" research; • improve decision-support, for example, research to improve vulnerability and adaptation assessments, operational predictions, and the understanding of decision-making processes; • improve the public's understanding of these issues, and into what interventions and mitigation strategies will be deemed acceptable to which constituencies; • estimate the costs of protecting health from the effects of climate change, including the characterisation of harmonized methods to estimate costs and benefits, the assessment of the health costs of inaction and the costs of adaptation, and improved economic assessment of the health co-benefits of climate and other environmental change mitigation [25,[130][131][132][133].…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting the tradition of systematic reviews in the health sciences, health-related adaptation was the focus of six articles (Walker et al 2011;Hosking and Campbell-Lendrum 2012;Bouzid et al 2013;Cheng and Berry 2013;Poutiainen et al 2013;Toloo et al 2013). The most dominant adaptation focus within which systematic reviews have penetrated has been reviewing lessons from, and trends in, adaptation governance (Hardee and Mutunga 2010;Berrang-Ford et al 2011;Ford et al 2011;Pearce et al 2011;Ford et al 2012a, b;Larsen et al 2012;Murtinho and Hayes 2012;Biesbroek et al 2013;Kamau and Mwaura 2013;Vink et al 2013).…”
Section: Systematic Review For Adaptation Research: Challenges and Comentioning
confidence: 99%
“…Consideration of context, processes, and mechanisms of causality may require more time commitment per document than extraction of key estimates or discrete items of information. Many realist or in-depth reviews, for example, are conducted using fewer than 50 articles, often 30-40 documents (Bouzid et al 2013;Cheng and Berry 2013;Kajan and Saarinen 2013;Linnenluecke et al 2013), and even in-depth qualitative systematic analyses with as few as 15-20 articles (Walker et al 2011;Toloo et al 2013). Research has shown that systematic review of complex and heterogeneous literature bases cannot rely solely on strict keyword searches (Greenhalgh and Peacock 2005), and this is likely to apply to many complex adaptation policy and practice questions.…”
Section: Literature and Information Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…An appraisal was conducted of the effectiveness of public health interventions directed at the climate-sensitive diseases through a systematic review of systematic reviews (Bouzid et al 2013). No reviews were found for nine of 17 of the high-priority climate-sensitive diseases.…”
Section: Managing New Climate-sensitive Health Threats In the Eumentioning
confidence: 99%